Agronomic characterization of Salvia hispanica L. germplasm - Xingú López, Andrés; Andrés; De la Cruz Torres, Eulogio; Sangerman-Jarquín, Dora María; Montes Hernandez, Salvador; Rubí Arriaga, Martin (Revista Mexicana de Ciencias Agrícolas, 2022)
Salvia hispanica L. (chia) is an herbaceous plant native to Mexico, belongs to the Lamiaceae family. The crop was banned and replaced by other cereals during the Conquest. Due to the nutritional content and nutraceutical properties it possesses, it has been reintroduced and is currently considered a highly nutritious potential food. The area sown is increased annually, the cultivated materials are usually local or introduced genotypes, because there are few improved varieties. With the aim of identifying outstanding accessions, oriented to greater efficiency of the crop, during the 2017 spring-summer agricultural cycle, 32 accessions of S. hispanica were agronomically characterized, in seven environments, under a design of randomized complete blocks with three repetitions. The following variables were evaluated: plant height, stem diameter, plant weight, number of spikes, grain weight per plant and yield per hectare. Accessions 1, 2, 12 and 22 had higher seed yield per ha, plant height, number of flower spikes, fruits per spike and dry plant weight. The average seed production was 924 kg ha-1. The best environment for chia production was Rancho San Lorenzo, Metepec. The cluster analysis grouped the accessions into five clusters, grouping them by their yield and related variables.